CUSTOMERS IN THE PERSPECTIVE OF QUALITY AND ITS IMPLEMENTATION IN EDUCATIONAL INSTITUTIONS - Habsi, Malikul; Affan, Moh.; Tijani, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Educational institutions have an important role in providing quality educational services to their customers, namely students, parents and the community. This research aims to examine the role of customers in determining the quality of educational services and to identify implementation strategies that can increase customer satisfaction in educational institutions. The research method used is qualitative research by conducting in-depth interviews and literature studies to understand the quality perspective from the customer's point of view. The research results show that this research makes an important contribution to educational institutions to improve service quality by understanding customer perspectives. The implications of this research finding can be used as a basis for designing policies and implementation strategies that are more effective in increasing customer satisfaction in educational institutions.